PENGARUH PEMASARAN BERDASARKAN PENGALAMAN, PEMASARAN EMOSIONAL TERHADAP LOYALITAS PELANGGAN - WULANSARI, DESSY (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: Traditional marketing concepts are considered to be less effective if used during such a relationship at present, so it takes the modern concept that is capable of create the emotions and experiences of visitors. Strategy concept is experiential marketing and emotional marketing. This research is quantitative approach. The research used causal research, experimental. The Target population in this research is visitors The Legend Waterpark was visiting over twice with the age between 16 to 25 years. Samples taken of 70 people. This research uses two types of samples, which is given treatment (experimental group) and not given treatment (control group). The technique sampling used quota sampling. Analysis of the multiple linear regression analysis is and independent sample t test. The Research result showed that experiential marketing and emotional marketing influence significantly to customer loyalty on two group. The experimen’s group showed greater customer loyalty levels than control’s group. Keywords: experiential marketing, emotional marketing, and customer loyalty.